Blue Lasing from Heavy‐Metal‐Free Colloidal Quantum Dots. Issue 2 (17th November 2022) - Wei, Huayu; Wei, Qi; Fang, Fan; Xiang, Guohong; Tong, Bingyi; Wang, Chenlin; Sun, Baoqing; Zhao, Xian; Li, Mingjie; Sun, Xiao Wei; Gao, Yuan
Abstract: Colloidal quantum dots (CQDs) have emerged as promising candidates for solution‐processed optical gain materials. Despite the substantial progress made with Cd or Pb‐contained CQDs, lasing from the environmentally friendly CQDs remains underexplored. Here, the highly emissive ZnSeTe/ZnSe/ZnS and ZnSe/ZnS CQDs is developed. The optical gain and lasing action from such Te‐alloyed and intrinsic ZnSe/ZnS CQDs across the blue spectral region is achieved. Te‐alloyed ZnSe core manifests a quasitype‐II band alignment with the ZnSe intermediate layer, favorable for suppressing the Auger recombination and also lasing wavelength tuning. The transient absorption spectroscopy reveals evidence of a blue optical gain with a threshold of one exciton per dot and a lifetime of 171 ps in the alloyed CQDs. Under a quasicontinuous‐wave pumping, lasing is observed from the blue CQDs in Fabry–Pérot cavities with a lower threshold fluence of 12.5 µJ cm −2 as compared with the traditional counterparts with heavy metals. The demonstration of heavy‐metal‐free CQD lasing opens up new opportunities in the application of CQDs as efficient and environmental‐friendly gain media. Abstract : ZnSe‐based colloidal quantum dots (CQDs) are environmentally friendly solution‐processable materials for efficient and tunable blue light emission. Via measuring transient absorption, it is confirmed that ZnSeTe/ZnSe/ZnS CQDs exhibit quasitype‐II band alignment, which aids the formation of optical gain. Blue lasing with super low‐threshold using such heavy‐metal‐free CQDs as the lasing medium in the Fabry–Pérot cavity is demonstrated.